Health and Economic Implications of Oil Spillage on Human Livelihood in Rivers State - Elijah B.U. Chigweyaru (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
This study examined the health and economic implications of oil spillage on human livelihood in Rivers State between 2014 and 2024. Anchored on the Relative Deprivation Theory developed by Merton (1938) and expanded by Runciman (1966), the study investigated two key objectives: to assess the effects of oil spillage on citizens’ health and to analyze its economic impact on human security. Two research questions guided the inquiry. The study adopted a mixed research design, employing both primary and secondary data through triangulation. A population of 2,886,660 was sampled using Taro Yamane’s formula to derive a sample size of 400. Data were collected through questionnaires, semi-structured interviews, and focus group discussions, validated through face and content validity tests, and analyzed with SPSS version 23 using simple percentage statistics. Findings revealed two major outcomes: first, that oil spillage led to severe health challenges, including respiratory illnesses, eye irritation, skin infections, gastrointestinal diseases, and suspected cancer cases; second, that oil pollution devastated economic activities by destroying farmlands, aquatic resources, and livelihoods, resulting in poverty, food insecurity, and declining educational access. The study concluded that oil spillage in Rivers State constitutes both a public health and economic emergency threatening human security. It recommended government-led environmental cleanup, expansion of rural health centres, equitable compensation to affected communities, and inclusion of local citizens in oil industry employment to mitigate suffering and restore sustainable livelihoods.